Concept analysis of diabetes-related quality of life - Anggi Lukman Wicaksana; Nuzul Sri Hertanti (Health and Quality of Life Outcomes)
Abstract Background Quality of life (QoL) is a common indicator of outcomes in people living with diabetes, but the concept of diabetes-related QoL (DRQoL) remains unclear. Clarifying core knowledge of DRQoL was the goal of this paper. Methods A concept analysis was conducted according to Walker and Avant’s framework. A systematic search of the published literature was conducted between 2002 and 2022 based on resource availability, current relevancy, and the quality of recent studies. Three major databases were used to identify the attributes, antecedents, consequences, and measures for DRQoL. Only articles investigating DRQoL among adult or elderly people living with diabetes that were published in English in peer-reviewed journals were analyzed. Results In total, 4342 articles were screened, and only 401 articles underwent eligibility assessment. A total of 183 articles were included in the analysis. Most (59.78%) of them were observational studies and DRQoL as a primary outcome. We identified four critical components of DRQoL: (a) general health, (b) diabetes-related satisfaction, (c) diabetes impact, and (d) diabetes self-management. The antecedents were classified according to their contributions to DRQoL as follows: 25 positive-induced, 4 neutral-based, and 19 negative-induced antecedents. The consequences of DRQoL were mortality risk, personal health, satisfaction with health care, hospitalization risk, and failure to return to work. The referents varied widely, and 32 tools were found for DRQoL measurement. Furthermore, 12 scales for disease-specific DRQoL and 17 tools for general QoL were identified. Conclusion This paper provides a definition of DRQoL as well as its attributes, antecedents, consequences, and measures in adults with diabetes. The attributes of DRQoL included general health, diabetes-related satisfaction, diabetes impact, and diabetes self-management. A comprehensive understanding of DRQoL can improve the quality of care and can aid in the recognition of the needs of care among people living with diabetes.